GOVERNMENT SYSTEM IN ISLAMIC LAW IN THE PERSPECTIVE OF FAZLUR RAHMAN - Lubis, Anugrah Al-Basyir (IBN KHALDUN BOGOR, 2023)
A nation-state that adheres to democracy is considered the best choice among the many options available, including countries with a majority Muslim population such as the Middle East. Muslim countries that used to be under the auspices of a system called the khilafah are now dividing themselves into small nations in the spirit of nationalism. Therefore, democracy is an option in the state system. The approach method used is a normative juridical approach. The type of this research is library research. In this case the researcher is dealing with texts or data that are directly usable and can be found in the library. The results of this research are in reading the present reality in the double movement asbabun nuzul macro is that the social context at the time thisverse was revealed was where the people needed a sense of security and peace after the migration from Mecca to Medina. Therefore, the initial interpretation of the Prophet Muhammad about power at that time was to make a joint consensus contained in the Medina Charter, and this became the first constitution in the history of Islamic civilization as the basis for living in society, nation and state. Modern reality is essentially the same, in that the basic human need to feel safe and secure in an area of authority must continue to be fulfilled. At the same time, the shape and nature that are currently changing are not a fundamental issue because the moral ideals in the nation-state and democratic system are still dialoguing with Islamic values itself.